Penerapan Media Sosial Instagram sebagai Promosi pada UMKM Warung RisolNimo Parompong Bandung Barat - Daniel Gmada Christiawan; Grace Orlyn Sitompul; Charles Surya Pratama Simangunsong; Perdana Silaban (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was conducted at the Warung RisolNimo MSME in Parompong, West Bandung, which had not yet utilized social media as a promotional medium. This condition limited marketing reach and resulted in low sales. This program aimed to optimize the use of Instagram as a more effective and structured digital promotional tool. The methods used included observation, interviews with business owners, Instagram account creation, visual identity design, and the preparation and management of promotional content. The implementation results showed an increase in account visibility with 425 views in 30 days, increased user interaction, and an increase in potential consumers who learned about the product through Instagram. Furthermore, there was an increase in the number of orders after consistent promotion. Thus, utilizing Instagram as a digital marketing strategy can increase brand awareness, expand market reach, and contribute to increasing MSME sales.